Electricity production from palm oil mill effluent (POME) through the integration of a microbial fuel cell and bilirubin oxidase-producing bacteria - Thipraksa, Junjira; Michu, Panisa; Chaijak, Pimprapa (Journal of Degraded and Mining Lands Management, 2023)
The microbial fuel cell (MFC) is a device that harnesses microbial metabolism to convert chemical energy into bio-electrical energy. Extensive research has demonstrated its efficacy in both wastewater treatment and power generation applications. This study focused on the integration of a microbial fuel cell (MFC) with a biocathode constructed using the oxidoreductase-producing bacterium Bacillus sp. MCO22 and rice straw as a cost-effective substrate. The MFC utilized palm oil mill effluent (POME) as a chemical energy source for electricity generation in the anodic chamber. The ability of the MFC was evaluated by monitoring biochemical oxygen demand (BOD) activity and electrochemical properties. Post-operation, chemical oxygen demand (COD) and color removal were measured. The results revealed that the MFC with the BOD-based cathode achieved a maximum current density and power density of 0.58±0.01 A/m2 and 0.17±0.00 W/m2, respectively. Furthermore, it exhibited high COD and color removal rates of 95.10±0.10% and 98.53±0.33%, respectively, without requiring an external power supply. This study presents novel insights into utilizing a BOD-producing bacterium as a whole-cell biocatalyst on the MFC cathodic surface for both electricity generation and agricultural wastewater treatment.